2015
DOI: 10.1111/padm.12142
|View full text |Cite
|
Sign up to set email alerts
|

Transparency in Public–private Partnerships: Not So Bad After All?

Abstract: Scholars' criticism of transparency in public–private partnerships (PPPs) often focuses on ‘external’ transparency, that is, the extent to which internal information is visible to the outside world. However, to achieve external transparency, internal transparency – the availability and inferability of information for the public procurer and the private party – is crucial. In this article we analyse input, process, and output transparency from three different perspectives (institutional, cognitive, and strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 39 publications
1
59
0
9
Order By: Relevance
“…Empirical insight on the enforcement of sanctions in the specific context of DBFMOs is absent. PPPs have been scrutinized in terms of strategic dilemmas and managerial behavior (Klijn & Teisman 2000;Van Ham & Koppenjan 2001;Edelenbos & Teisman 2008); effectiveness, cost-efficiency, and economic performance (Parker & Hartley 2003;Välilä 2005); accountability (Willems & Van Dooren 2011); transparency (Reynaers & Grimmelikhuijsen 2015); legitimacy (Hodge 2006); and public values (Charles et al 2007;Reynaers 2014). Regulation studies mainly focus on instruments that help to ensure the regulatory goals of governments regarding businesses and their customers in the context of competitive markets in areas such as telecommunication (Jordana & Levi-Faur 2004;Tambini et al 2007), energy supply (Cameron & Brothwood 2002), and financial markets (Davies & Green 2008).…”
mentioning
confidence: 99%
“…Empirical insight on the enforcement of sanctions in the specific context of DBFMOs is absent. PPPs have been scrutinized in terms of strategic dilemmas and managerial behavior (Klijn & Teisman 2000;Van Ham & Koppenjan 2001;Edelenbos & Teisman 2008); effectiveness, cost-efficiency, and economic performance (Parker & Hartley 2003;Välilä 2005); accountability (Willems & Van Dooren 2011); transparency (Reynaers & Grimmelikhuijsen 2015); legitimacy (Hodge 2006); and public values (Charles et al 2007;Reynaers 2014). Regulation studies mainly focus on instruments that help to ensure the regulatory goals of governments regarding businesses and their customers in the context of competitive markets in areas such as telecommunication (Jordana & Levi-Faur 2004;Tambini et al 2007), energy supply (Cameron & Brothwood 2002), and financial markets (Davies & Green 2008).…”
mentioning
confidence: 99%
“…One way to think about kinds of information for a PPP is around inputs, processes, outputs, and outcomes. This typology is based on the article on transparency in PPPs by Reynaers and Grimmelikhuijsen, 10 although I have added one category (outcomes) and altered the definitions (to fit with standard terms used in the evaluation and management literature). Inputs include the contributions from each partner, such as finances and sources of funding, materials purchased and received by the organization, people who work at the PPP (human resources), as well as any intellectual property and information used by the partnership.…”
Section: Transparencymentioning
confidence: 99%
“…11 In their analysis of four partnerships in The Netherlands, Reynaers and Grimmelikhuijsen found that there was limited attention to inputs and processes; most of the attention focused on outputs, but the output targets were not always clearly specified (which created problems). 10 The quality and scope of information is also often decided by the partnership. For instance, monitoring information on outputs produced by the PPP is often published in an annual report and made available to the general public.…”
Section: Transparencymentioning
confidence: 99%
“…According to Schaeffer and Loveridge (2002) [48], the differences in characteristics of PPP arrangements that are important to their success or failure are overlooked. The availability of information does not mean that decision maker or/and stakeholders will be able to assess information and extrapolate underlying subliminal trends [49,50].…”
Section: Ppp In Russia and International Experiencementioning
confidence: 99%